POPULATION DYNAMICS AND mE MANAGEMENT OF THE CoMMERCIAL SHRIMP PENAEVS SEMISULCATUS FROM THE BAY OF BENGAL (Biological Sciences - PJSIR, 2003)
FiSAT programme was used to estimate  population  parameters  of  Penaeus  semis11/catus  from  length  frequency  data  based computer programme . Lo: and K for male and female ·were found  to be 23.5 cm  and 27.0 cm; and 0.8 yea(1  and  0.9 yea r- 1 respectively. The estimate provided by Wetherall plot for Lo: was 23.224 cm and 27.258 cm for male and female respectively. An additional estimate of Z/K was 4.688 for male and 5.373 for female. The growth pe1forma11ce index was 2.654 and  2.817 for male and female respectively.  The annual  rate of natural  and  fishing mortality  were estimated  as  1 .73,3.47 for male and 1 .72, 2.98 for female respectively. The exploitation rates were 0.67 and 0.63 for male  and  female respectivel y. The selection pattern Le for male was 15.88 cm and  for  female  18.869 cm. Recruitment  pattern  suggestive  was one even seasonal pulse during June, July and August. Peak recruitment appeared in July. Yield-per-recruit analysis suggested that the investigated stocks are overexploited.  Yield-per-recruit  isopleths suggested  that  length  at  first  capture was 12.0 cm (male) and 13.52 cm (female)  without  depletion  of  spawning  stock.  The  relationship  between  total  length and body weight were found to be W = 0.01 167 Tl,2 8956 for male and W = 0.011028  TL2 9218  for  female.  Highest exploitation was observed between length  class  15.0 to  19.0 cm  for male and between  18.0 to 23.0 cm  for female. Yield  and Stock Prediction  analysis suggested  that the highest yield  and price could  be achieved  by  simultaneously  decreasing  the  fishing  mortality  to  1.5 coefficient rate.